Artificial Intelligence (and Public Administration) - Criado, J. Ignacio (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
Algorithms and Artificial Intelligence (AI) in the public sector have been adopted in different contexts. Conceptually, the implications of AI and algorithms in public administration are still unclear. However, different international organizations have defined a series of ethical principles and legal issues to take into account. The European Union institutions have become a key player in guiding the adoption of AI, setting the first guidelines for public policies at the national level. The Spanish Government has developed a strategy according to these lines, albeit with those responsible for implementation having their own perceptions and priorities. Hence, this paper begins with the following descriptive and exploratory questions: How are the main international organizations framing AI ethically and legally? What is the framework of priorities of the AI policy endorsed by the Government of Spain in connection with the European Union? What is the perception about AI by IT managers (CIOs) in ministries? To answer these questions, this study is based on a documentary analysis and part of the results of a survey about the perceptions of public managers responsible for IT implementation in Spanish ministries. Our analysis encompasses an exploratory answer to the research questions guiding the study. In addition, the results indicate some key issues in designing policies and strategies to use AI in different politico-administrative contexts.